An Evaluation of the Role of the Radiologist and Surgeon in the Management of Hepatic Trauma at Qazi Hussain Ahmad Hospital, Nowshera, kpk - Kamran Ahmad, Erum Habib, Zarlakhtha Zahir, Humera Habib, Rashda Khattak, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: This study aims to compare the surgical results and CT scan findings in patients with hepatic trauma to evaluate the sensitivity and usefulness of sonographic data. Study Design: A Single-center study. Study duration : From Jan 2020 to Feb 2021, the Radiology and Surgery Divisions at Qazi Hussain Ahmad Hospital in Nowshera. Methods: There will be a retrospective chart review of all patients suspected of having sustained hepatic injuries admitted to the surgical department From Jan 2020 to Feb 2021 and subsequently present to the department of Radiology. There were two groups of patients: Group I, who had surgical intervention, and Group II, who were hospitalized and treated non-operatively. Prospective cohort research in which the sonographer and clinicians who analyzed emergency sonograms compiled data from all patients. Patients injured in their livers within this time frame were tracked down. Results: Overall, 291 patients (72% of the sample) were included in the study, with 83 patients (29% of the sample) requiring surgical intervention and 208 patients (71% of the model) being handled conservatively. All Group-06 patients had CT scans. Of the 83 patients who had surgery, 11 were classified as having a Grade-1 complication, 12 as having a Grade-11 difficulty, 44 as having a Grade-Ill complication, 18 as having a Grade-IV complication, and three as having a Grade-V complication. In a study with 208 patients who did not have surgery, 15 (73%) had a Grade-I fall, and 56(28%) experienced a Grade-11 fall. Sonographic data and surgical results in individuals who have had surgery, and how they compare and contrast. Cconclusion: Ultrasonography is the most sensitive method for determining the severity of liver damage caused by forceful abdominal trauma. Since it may be done at the bedside and repeated as needed, it serves as a primary diagnostic strategy in these patients and helps when paracentesis is necessary. Keywords: Abdominal injury, Shortened Surgical Terminology for Liver Trauma (AST), liver trauma grades, CT scan, bleed, liver injury,